Perilaku Konsumtif Generasi Z terhadap Keputusan Pembelian Produk Silverqueen di Kota Sidoarjo - Rizaldi Ahmad Sutarno; Sugeng Purwanto (Universitas Batanghari, 2022)
Generation Z feels comfortable in the virtual world, where most of generation Z is the child of generation X which used to be a market group that was highly monitored by the market in the sense that their consumption is controlled by the liveliness producers of generation Z has an impact on the behavior to buy an item for its own pleasure, not out of necessity or known as consumptive behavior or consumerism. SilverQueen's new flavor choices are inspired by generation Z characters who are bold, passionate, and free to explore new things. The implication is that the decline in revenue in silverqueen, one of which relates to purchasing decisions. The purpose of this study was to find out the influence between the consumptive behavior of generation z on the decision to buy silverqueen products in the city of Sidoarjo. This type of research uses a descriptive quantitative approach. The study sample is generation z in the city of Sidoarjo age criteria 10-24 years. The results of this study showed that there was a positively significant influence between consumptive behavior on purchasing decisions of 0.587530. R-Square value of 34.51% While the remaining 65.49% is explained by other variables outside the study